Changing roles of CD3+CD8low T cells in combating HIV-1 infection - Xin Zhang; Xiuwen Wang; Ling Qin; Xiaofan Lu; Zhiying Liu; Zhen Li; Lin Yuan; Rui Wang; Junyan Jin; Zhenglai Ma; Hao Wu; Yonghong Zhang; et al. (Chinese Medical Journal, 2023)
Abstract. Background:. Cluster of differentiation 8 (CD8 T) cells play critical roles in eradicating human immunodeficiency virus (HIV)-1 infection, but little is known about the effects of T cells expressing CD8 at low levels (CD8low) or high levels (CD8high) on HIV-1 replication inhibition after HIV-1 invasion into individual. Methods:. Nineteen patients who had been acutely infected with HIV-1 (AHI) and 20 patients with chronic infection (CHI) for ≥2 years were enrolled in this study to investigate the dynamics of the quantity, activation, and immune responses of CD3+CD8low T cells and their counterpart CD3+CD8high T cells at different stages of HIV-1 infection. Results:. Compared with healthy donors, CD3+CD8low T cells expanded in HIV-1-infected individuals at different stages of infection. As HIV-1 infection progressed, CD3+CD8low T cells gradually decreased. Simultaneously, CD3+CD8high T cells was significantly reduced in the first month of AHI and then increased gradually as HIV-1 infection progressed. The classical activation of CD3+CD8low T cells was highest in the first month of AHI and then reduced as HIV-1 infection progressed and entered the chronic stage. Meanwhile, activated CD38−HLA-DR+CD8low T cells did not increase in the first month of AHI, and the number of these cells was inversely associated with viral load (r = −0.664, P = 0.004) but positively associated with the CD4 T-cell count (r = 0.586, P = 0.014). Increased programmed cell death protein 1 (PD-1) abundance on CD3+CD8low T cells was observed from the 1st month of AHI but did not continue to be enhanced, while a significant T cell immunoreceptor with immunoglobulin and immunoreceptor tyrosine-based inhibition motif (ITIM) domains (TIGIT) abundance increase was observed in the 12th month of infection. Furthermore, increased PD-1 and TIGIT abundance on CD3+CD8low T cells was associated with a low CD4 T-cell count (PD-1: r = −0.456, P = 0.043; TIGIT: r = −0.488, P = 0.029) in CHI. Nonetheless, the nonincrease in PD-1 expression on classically activated CD3+CD8low T cells was inversely associated with HIV-1 viremia in the first month of AHI (r = −0.578, P = 0.015). Notably, in the first month of AHI, few CD3+CD8low T cells, but comparable amounts of CD3+CD8high T cells, responded to Gag peptides. Then, weaker HIV-1-specific T-cell responses were induced in CD3+CD8low T cells than CD3+CD8high T cells at the 3rd and 12th months of AHI and in CHI. Conclusions:. Our findings suggest that CD3+CD8low T cells play an anti-HIV role in the first month of infection due to their abundance but induce a weak HIV-1-specific immune response. Subsequently, CD3+CD8low T-cell number decreased gradually as infection persisted, and their anti-HIV functions were inferior to those of CD3+CD8high T cells.